The role of Hartmann’s procedure in the elective management of rectal cancer: results of a Brazilian cohort study - LAZZARON,ANDERSON RECH (2021)
ABSTRACT Background: although preservation of bowel continuity is a major goal in rectal cancer surgery, a colorectal anastomosis may be considered an unacceptably high-risk procedure, particularly for patients with multiple comorbidities. We aimed to assess rates of surgical complications in rectal cancer patients according to the type of procedure they had undergone. Materials and Methods: this cohort included all rectal cancer patients undergoing elective resection at a referral academic hospital over 16 years. There were three study groups according to the type of performed operation: (1) rectal resection with anastomosis without defunctioning stoma (DS); (2) rectal resection with anastomosis and DS; and (3) Hartmann’s procedure (HP). Postoperative complications and clinical outcomes were assessed. Results: four-hundred and two patients were studied. The 118 patients in group 3 were significantly older (>10 years), had higher Charlson Comorbidity Index scores, and more ASA class ≥3 than patients in the other two groups. Sixty-seven patients (16.7%) had Clavien-Dindo complications grade ≥ III, corresponding to an incidence of 11.8%, 20.9%, and 14.4% in groups 1, 2, and 3, respectively (p=0.10). Twenty-nine patients (7.2%) had major septic complications that required reoperation, with an incidence of 10.8%, 8.2% and 2.5% in groups 1, 2 and 3, respectively (p=0.048). Twenty-one percent of the group 2 patients did not undergo the stoma closure after a 24-month follow-up. Conclusion: HP was associated with a lower incidence of reoperation due to intra-abdominal septic complications. This procedure remains an option for patients in whom serious surgical complications are anticipated.